The Mechanism of Chromatin Remodeler SMARCAD1/Fun30 in Response to DNA Damage - Tong, Ze-Bin; Ai, Hua-Song; Li, Jia-Bin (Frontiers in Cell and Developmental Biology, 2020)
DNA packs into highly condensed chromatin to organize the genome in eukaryotes but occludes many regulatory DNA elements. Access to DNA within nucleosomes is therefore required for a variety of biological processes in cells including transcription, replication, and DNA repair. To cope with this problem, cells employ a set of specialized ATP-dependent chromatin-remodeling protein complexes to enable dynamic access to packaged DNA. In the present review, we summarize the recent advances in the functional and mechanistic studies on a particular chromatin remodeler SMARCAD1Fun30 which has been demonstrated to play a key role in distinct cellular processes and gained much attention in recent years. Focus is given to how SMARCAD1Fun30 regulates various cellular processes through its chromatin remodeling enzyme activity, and especially the regulatory role of SMARCAD1Fun30 in gene expression control, maintenance and establishment of heterochromatin, and DNA damage repair. Moreover, we review the studies on the molecular mechanism of SMARCAD1Fun30 that promotes the DNA end-resection on double-strand break ends, including the mechanisms of recruitment, activity regulation and chromatin remodeling.